Prognostic implication of mucinous histology in colorectal cancer patients treated with adjuvant FOLFOX chemotherapy - Lee, D-W (Nature Publishing Group, 2013)
BACKGROUND: There have been controversies in prognostic impact of mucinous histology on colorectal cancer, and its implication in patients treated with adjuvant 5-fluorouracil, leucovorin, and oxaliplatin (FOLFOX) is unclear. METHODS: Stage II and III colorectal cancer patients who underwent curative resection followed by adjuvant FOLFOX were included. Patients were grouped according to the mucinous content: >50%, mucinous adenocarcinoma (MAC); <50%, adenocarcinoma with intermediated mucinous component (AIM); and without any mucinous component, non-MAC (NMA). Clinicopathological features and disease-free survival (DFS) were compared. RESULTS: Among a total of 521 patients, 27 patients (5.2%) had MAC, 41 patients (7.9%) had AIM, and 453 patients (86.9%) had NMA. Mucinous adenocarcinoma and AIM had higher frequency of proximal location and microsatellite instability, but lower frequency of angiolymphatic invasion. Disease-free survival was significantly worse in the MAC compared with NMA (3-year DFS 57% and 86%, respectively; P<0.001) and AIM (3-year DFS 87%, P=0.01 vs MAC). Multivariate analysis revealed MAC as an independent negative prognostic factor of DFS (adjusted hazard ratio 7.96, 95% confidence interval 3.76–16.8). CONCLUSION: Adenocarcinoma with intermediated mucinous component and MAC have distinct clinicopathological features compared with NMA. Mucinous adenocarcinoma has an adverse prognostic impact on stage II or III colorectal cancer treated with adjuvant FOLFOX.